2014
DOI: 10.1039/c4sc01035c
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium–ligand cooperation promotes selective dehydrogenation of formic acid to H2 and CO2

Abstract: Selective conversion of formic acid to H2 and CO2 is catalysed by a molecular aluminum complex. Metal–ligand cooperative interactions stabilize a transition state for an outer-sphere β-hydride abstraction mechanism for catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
132
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 44 publications
5
132
0
1
Order By: Relevance
“…Sufficiently acidic substrates (p K a ∼16) will liberate H 2 upon protonolysis of the Al–hydride when a second equivalent of substrate is added 29. This second reaction pathway has been observed by us with water, tosylamine, and formic acid, amongst others.…”
Section: Ligand‐based Proton Transfer At Aluminum Complexesmentioning
confidence: 55%
“…Sufficiently acidic substrates (p K a ∼16) will liberate H 2 upon protonolysis of the Al–hydride when a second equivalent of substrate is added 29. This second reaction pathway has been observed by us with water, tosylamine, and formic acid, amongst others.…”
Section: Ligand‐based Proton Transfer At Aluminum Complexesmentioning
confidence: 55%
“…[23] Also the last s-bond metathesis step in the cycle seemed questionable.Acomprehensive calculational study, however, demonstrated that the metal hydride mechanism shown in Scheme 1isfeasible. [15,18,[31][32][33][34][35][36][37][38][39][40][41][42] Especially noteworthy are two very recent investigations on LiAlH 4 -catalyzed alkene and aldehyde/ketone hydroboration. Acrucial step is the hydrogenolysis of the metal À Cbond by H 2 ,for which the rate is known to decrease with decreasing bond ionicity:N a À C > Mg À C > Al À C. [25] since it is well-known that RNH 2 and R 2 NH react smoothly with LiAlH 4 to give aluminium amide products and H 2 , [26][27][28][29][30][31] hydrogenolysis of AlÀNbonds to give amines is anticipated to be even more cumbersome.S ubstitution of H 2 for polar borane or silane reductants was therefore al ogical step.…”
mentioning
confidence: 99%
“…Indeed, hydroboration and hydrosilylation reactions were found to be more promising. [15,41,42] Herein, we introduce LiAlH 4 , which is normally applied as astoichiometric reducing agent, as as imple catalyst for imine reduction using the bulk commodity H 2 at ac onvenient 1bar pressure (Table 1). [15,18,[31][32][33][34][35][36][37][38][39][40][41][42] Especially noteworthy are two very recent investigations on LiAlH 4 -catalyzed alkene and aldehyde/ketone hydroboration.…”
mentioning
confidence: 99%
“…We 2À is ap henyl-substituted bis(imino)pyridine ligand) can be protonated three times.O ne of these protons reacts with the Al hydride to afford H 2 ,a nd the other two protons react with the ligand (Scheme 1). [12] We now focus on ligand reactivity only,and report herein that the analogous aluminum chloride complex [( Ph I 2 P 2À )Al-(THF)Cl] (1,S cheme 2) [13] promotes H 2 production from protons in the presence of an applied reducing potential. We also discuss [( Ph I 2 P 1À )AlCl 2 ]( 2), [14] where the After addition of two equivalents of 2,6-lutidinium acid (lutH + )t oasolution of 1,t wo reduction events were observed, namely at À0.95 Va nd À1.20 V, and the anodic shift of these events compared with reduction of 1 (À1.55 V) is consistent with the additional positive charge on the complex resulting from protonation of the ligand (Figure 1a).…”
Section: Akeyareaofresearchintofuel-producingelectrocatalystsismentioning
confidence: 98%